The analysis of the calculation process related to labyrinth sealing with extraction - Joachimiak, Damian; Joachimiak, Magda; Krzyślak, Piotr (Zielona Góra: Uniwersytet Zielonogórski)
The work presents a calculation process enabling one-dimensional numerical calculations of labyrinth sealing. A DSV program determines the thermodynamic parameters of gas in the sealing chambers with extraction. The influence of the sealing length upon the stability of a matrix solution of the system of equations with the use of Cond(C) parameter is analysed. Next, the operation of the software extended with a module that enables determination of the initial pressure p0, to which the assumed mass flow for a set geometry and sealing length would correspond is discussed.
Keywords: labyrinth seals; turbomachines; fluid-flow machines; method of calculation labyrinth seals